Quantification of PAH4 in roasted cocoa beans using QuEChERS and dispersive liquid-liquid micro-extraction (DLLME) coupled with HPLC-FLD - Agus, Baizura Aya Putri; Hussain, Norhayati; Selamat, Jinap (Elsevier, 2020)
Roasting is an important process in cocoa production which may lead to formation of non-desirable compounds such as polycyclic aromatic hydrocarbons (PAHs). Therefore, PAH4 (sum of four different polycyclic aromatic hydrocarbons; benz[a]anthracene, chrysene, benzo[b]fluoranthene, and benzo[a]pyrene) in roasted cocoa beans was determined using a modified method (combination of QuEChERS and DLLME), and quantified by HPLCFLD. The modified method was validated and met the performance criteria required by the EU Regulation (No. 836/2011). Results show a significant (p < 0.05) increase of PAH4 (0.19–7.73 ng/g) with an increase in temperatures (110–190 °C) and duration (10–50 min). The PAHs content in whole cocoa bean roasting was detected even at the lowest temperature (110 °C) compared to nib roasting detected at 150 °C which indicates that PAHs was transferred from dried shells to roasted cocoa beans during the roasting process. The data obtained may help to control and minimize PAH4 formation during cocoa processing.